Incentives and the diffusion of agricultural knowledge: experimental evidence from northern Uganda - Shikuku, Kelvin Mashisia; Pieters, Janneke; Bulte, Erwin; Läderach, Peter R.D. (Wiley, 2019)
We present results of a randomized evaluation that assesses the effects of different incentives for diffusion of agricultural knowledge by smallholders in northern Uganda. Randomly-selected disseminating farmers (DFs) from a large sample of villages are assigned to one of three experimental arms: (a) training about climate smart agriculture, (b) training plus a material reward for knowledge diffusion, and (c) training plus a reputational gain for knowledge diffusion. We find that leveraging somebody’s reputation (or social recognition) has a positive impact on DFs’ experimentation and diffusion effort. This impact is stronger than that measured in the private material rewards treatment.